The Mediating Effect of Patient Satisfaction in the Influence of Service Quality on Patient Loyalty at the Dr. Soekardjo Tasikmalaya Regional General Hospital - Peni Cahyati; Yanyan Bahtiar; Novi Indriani (Greenation Research & Yayasan Global Resarch National, 2025)
Introduction: Competition in the healthcare industry requires hospitals to not only provide quality medical services but also build patient loyalty as the key to long-term sustainability. This study aims to analyze the influence of service quality on patient loyalty with patient satisfaction as a mediating variable at Dr. Soekardjo General Hospital in Tasikmalaya. Methods: The research method used a quantitative approach with a survey of 100 patient respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results: The results indicate that service quality has a positive and significant effect on patient satisfaction (path coefficient = 0.579; p < 0.05) and patient loyalty (path coefficient = 0.317; p < 0.05). Additionally, patient satisfaction also positively influences patient loyalty (path coefficient = 0.386; p < 0.05). Another important finding is that patient satisfaction significantly mediates the relationship between service quality and patient loyalty. Thus, improving service quality enhances satisfaction, which ultimately strengthens patient loyalty. Conclusion: The implications of this study emphasize the importance of hospital strategies in providing services that are not only efficient but also create emotionally satisfying experiences to build long-term loyalty.